Formy powiązań podmiotów gospodarczych w świetle standardów rachunkowości oraz krajowych regulacji prawnych - przegląd dotychczasowego dorobku teoretycznego - Tatarska, Marzena (Forms of Relations between Businesses in Terms of Accounting Standards and Polish Legal Regulations: an Outline of Existing Theoretical Studies, 2005)
The article presents different forms of cooperation between companies with special emphasis of the variety of terms describing relations between businesses coined by economical sciences. Within mutually interrelated businesses significant differences can occur in structure, durability and intensity of these relations. The article refers to legislature and surveys the most important Polish legal acts concerning relations among businesses. International Accounting Standards have also been mentioned, as a comprehensive and extensive resource of business relations. The article takes a descriptive approach, identifying and defining particular forms of business relations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 337-351